Tumor Microenvironment in Head and Neck Squamous Cell Carcinoma: A Focus on Tumor-Infiltrating Lymphocytes - Norouzian, Marzieh; Balouchi-Anaraki, Sima (Asian Pacific Journal of Cancer Biology, 2019)
For more progress in head and neck squamous cell carcinoma (HNSCC) immuno-oncology, further understanding of interactions between tumor and immune system as well as factors in the tumor microenvironment is required. HNSCC is seriously infiltrated by lymphocytes but is known to be highly immunosuppressive. The aim of this review is to highlight the complexity of tumor microenvironment and tumor- immune cells interaction in the HNSCC, in order to improve understanding of tumorigenesis and disease progression in HNSCC patient and to provide valuable information about prognostic markers. The main goal of this review is to discuss the role of the tumor infiltrating lymphocytes in tumor progression, their cross-talk with other components of the tumor microenvironment as well as their roles in carcinogenesis, metastasis process, treatment, and prognosis in head and neck squamous cell carcinomas.